Nomogram Prediction Model for Diabetic Retinopathy Development in Type 2 Diabetes Mellitus Patients: A Retrospective Cohort Study. (21st September 2021) - Chen, Xiaomei; Xie, Qiying; Zhang, Xiaoxue; Lv, Qi; Liu, Xin; Rao, Huiying
Abstract : Background . This study is aimed at investigating the systemic risk factors of diabetic retinopathy and further establishing a risk prediction model for DR development in T2DM patients. Methods . This is a retrospective cohort study including 330 type 2 diabetes mellitus (T2DM) patients who were followed up from December 2012 to November 2020. Multivariable cox regression analysis identifying factors associated with the hazard of developing diabetic retinopathy (DR) was used to construct the DR risk prediction model in the form of nomogram. Results . 50.6% of participants (mean age: 58.60 ± 10.55 ) were female, and mean duration of diabetes was 7.09 ± 5.36 years . After multivariate cox regression, the risk factors for developing DR were age (HR 1.068, 95%Cl 1.021-1.118, P = 0.005 ), diabetes duration (HR 1.094, 95%Cl 1.018-1.177, P = 0.015 ), HbA1c (HR 1.411, 95%Cl 1.113-1.788, P = 0.004 ), albuminuria (HR 6.908, 95%Cl 1.794-26.599, P = 0.005 ), and triglyceride (HR 1.554, 95%Cl 1.037-2.330, P = 0.033 ). The AUC values of the nomogram for predicting developing DR at 3-, 4-, and 5-year were 0.854, 0.845, and 0.798. Conclusion . Combining age, diabetes duration, HbA1c, albuminuria, and triglyceride, the nomogram model is effective for early recognition and intervention of individuals at high risk of DR development.